The Effect of Strokemash Training Method with Play Training Method on the Smash Ability of Badminton Players of SMPN 4 Koto Baru - Abdul Sattar; Dian Estu Prasetyo; Maldin Ahmad Burhan (The Future of Education Journal, 2023)
The purpose of this study was to determine the effect of the stroke smash training method and the playing practice method on the smash ability of badminton players at SMP N 4 Koto Baru. This research is a type of quantitative research using an experimental method approach. While the form of research design used is "one-group pretest-posttest design". The population in this study were students of class VIII SMP N 4 Koto Baru with a total of 31 students. The samples in this study were male and female class VIII students who were in good health and had no history of serious illness and were willing to take part in the treatment during the research. The specified assessment that fulfilled was 19 people. The data analysis technique used in this study is the normality test and hypothesis testing. The results showed that the influence of the smash hitting training method on the smash ability of badminton players at SMP N 4 Koto Baru obtained t count of 2.1185 and t table of 1.8595 which means t count > t table. Based on the hypothesis testing criteria, namely Ho is accepted. So in this study it was concluded that there was an influence of the smash practice method on the smash ability of the badminton players of SMP N 4 Koto Baru which was accepted at a significant level of 0.05 and tested the truth in this study, the influence of the playing practice method on the smash ability of the badminton players of SMP N 4 Koto Baru gave the result t count of 3.1167 and t table of 1.8331, which means t count > t table. Based on the hypothesis testing criteria, namely Ha accepted. So in this study it was concluded that there was an influence of the playing practice method on the smash ability of badminton players at SMP N 4 Koto Baru and the truth was tested in this study. the results of the study between groups A and B had different improvement results, that group B was better than group A on the badminton smash ability of SMP N 4 Koto Baru players